OPPORTUNITIES FOR OPTIMIZATION OF DRUG THERAPY BY ENDOTHELIN RECEPTOR ANTAGONISTS FOR THE PATIENT WITH IDIOPATHIC PULMONARY ARTERIAL HYPERTENSION AND ATRIAL SEPTOSTOMY - V. V. Gramovich; A. M. Aleevskaya; T. V. Martynyuk (Евразийский Кардиологический Журнал, 2018)
The initiation of PAH-specific therapy in this case of IPAH was preceded by atrial septostomy. The chosen treatment plan put the patient at an unacceptable risk and did not contribute to the improvement of her clinical condition. The clinical case described in the paper demonstrates the importance of a reasonable approach to the implementation of palliative surgical interventions in patients with pulmonary hypertension in accordance with modern guidelines, as well as the possibility of optimizing drug therapy with endothelin receptor antagonists.